HsdR Subunit of the Type I Restriction-Modification Enzyme EcoR124I: Biophysical Characterisation and Structural Modelling - Obarska-Kosinska, Agnieszka (Elsevier, 2008)
Type I restriction-modification (RM) systems are large, multifunctional enzymes composed of three different subunits. HsdS and HsdM form a complex in which HsdS recognizes the target DNA sequence, and HsdM carries out methylation of adenosine residues. The HsdR subunit, when associated with the HsdS-HsdM complex, translocates DNA in an ATP-dependent process and cleaves unmethylated DNA at a distance of several thousand base-pairs from the recognition site. The molecular mechanism by which these enzymes translocate the DNA is not fully understood, in part because of the absence of crystal structures. To date, crystal structures have been determined for the individual HsdS and HsdM subunits and models have been built for the HsdM–HsdS complex with the DNA. However, no structure is available for the HsdR subunit. In this work, the gene coding for the HsdR subunit of EcoR124I was re-sequenced, which showed that there was an error in the published sequence. This changed the position of the stop codon and altered the last 17 amino acid residues of the protein sequence. An improved purification procedure was developed to enable HsdR to be purified efficiently for biophysical and structural analysis. Analytical ultracentrifugation shows that HsdR is monomeric in solution, and the frictional ratio of 1.21 indicates that the subunit is globular and fairly compact. Small angle neutron-scattering of the HsdR subunit indicates a radius of gyration of 3.4 nm and a maximum dimension of 10 nm. We constructed a model of the HsdR using protein fold-recognition and homology modelling to model individual domains, and small-angle neutron scattering data as restraints to combine them into a single molecule. The model reveals an ellipsoidal shape of the enzymatic core comprising the N-terminal and central domains, and suggests conformational heterogeneity of the C-terminal region implicated in binding of HsdR to the HsdS–HsdM complex.